Productive and Reproductive Efficiency of Red Chittagong Cattle Under Farm Condition - Mostari, MP; Huque, KS; Hasanat, MS; Gulshan, Z (Progressive Agriculture, 2014)
The productive and reproductive efficiency of Red Chittagong cattle (RCC) reared at the Bangladesh Livestock Research Institute (BLRI) farm was evaluated. A total of 46 RCC of different categories were considered under this study. Parameters studied were birth weight, weight at 3, 6 months of age and adult body weight, growth rate, daily milk yield, lactation length, lactation yield, age at puberty, weight at puberty, age at first calving, post partum estrus period, service per conception, calving interval and gestation length of RCC were collected and recorded. The birth weight differed significantly (p<0.01) between male and female and the average birth weight of RCC calves at farm level was 14.87 kg. The growth rates and adult body weight also differed significantly (p<0.05 and p<0.01) between male and female except in growth rate from 3 to 6 months of age. The average daily milk yield, milk yield per lactation and lactation length of RCC were 2.24 kg, 526.81 kg and 238 days, respectively. The age at puberty, service per conception, post partum estrus period and calving interval of RCC heifers and cows were 15 months, 1.15, 40 days and 11 months, respectively. It can be concluded that the RCC is a genetically and economically superior variety of Bangladesh. DOI: http://dx.doi.org/10.3329/pa.v18i2.18166 Progress. Agric. 18(2): 109 - 114, 2007